Modeling determinants of tourism demand in Colombia (2020)
Purpose – This paper estimates the determinants of international tourist arrivals to Colombia from 1995 to 2014. Design – Tourist demand is related to interlinking relationships between origins and destinations. The international movement of travelers has grown exponentially in recent decades, and these dynamics have affected Colombia as well. Methodology/Approach – We propose a generalized linear mixed model, with a consideration of factors from the theory of consumer choice and those approached from the perspective of new economic geography. Findings – Apart from purchasing power and institutional factors as facilitators of travel, we found that general aspects of the country (such as language and geographical proximity) directly affect the flow of visitors, whereas exchange differences and physical distance reduce tourist attraction. Originality of the research – Estimation of tourist flows will serve as a diagnostic and planning tool for developing proposals of tourism attractiveness related to different environment. Keywords tourism demand, tourist flows, generalized linear mixed model, developing countries